2014
DOI: 10.1002/ptr.5206
|View full text |Cite
|
Sign up to set email alerts
|

Eugenia punicifolia (Kunth) DC. as an Adjuvant Treatment for Type‐2 Diabetes Mellitus: A non‐Controlled, Pilot Study

Abstract: Type-2 diabetes mellitus (DM) is a highly prevalent disease with significant morbidity and mortality around the world. However, there is no universally effective treatment, because response to different treatment regimens can vary widely among patients. In this study, we aimed to investigate whether the use of the powdered dried leaves of Eugenia punicifolia (Kunth) DC. (Myrtaceae) is effective as an adjuvant to the treatment of patients with type-2 DM. Fifteen patients were enrolled in a pilot, non-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…The MS/MS fragmentation produced a deprotonated aglycone ion at m/z 301 [M-146-H] − due loss a sugar moiety of 146 Da and m/z 271 typical of flavon-3- O -monoglycoside [ 41 ] and 179 from RDA of ring A. Two isomeric compounds ions observed with [M–H] − at m/z 463, whose MS/MS main fragmentation produced a deprotonated aglycone form myricetin ion at m/z 317 [M-146-H] − (loss of a sugar moiety of 146 units), indicates that the compound is a myricetin monohexoside (myricetin 3-O-galactoside or myricetin 3-O-rhamnoside) and another isomer peak ion at m/z 301 with its [M-162-H] − (loss of a sugar moiety of 162 units), an indicative of quercetin monohexoside, and the hexose could be glucoside or galactoside [ 42 ]. Dissociation of fragment m/z 593 showed a loss of 308 units (corresponding to a rhamnose plus glucose group) and yielded directly a fragment ion at m/z 285 (assigned as kaempferol).…”
Section: Resultsmentioning
confidence: 99%
“…The MS/MS fragmentation produced a deprotonated aglycone ion at m/z 301 [M-146-H] − due loss a sugar moiety of 146 Da and m/z 271 typical of flavon-3- O -monoglycoside [ 41 ] and 179 from RDA of ring A. Two isomeric compounds ions observed with [M–H] − at m/z 463, whose MS/MS main fragmentation produced a deprotonated aglycone form myricetin ion at m/z 317 [M-146-H] − (loss of a sugar moiety of 146 units), indicates that the compound is a myricetin monohexoside (myricetin 3-O-galactoside or myricetin 3-O-rhamnoside) and another isomer peak ion at m/z 301 with its [M-162-H] − (loss of a sugar moiety of 162 units), an indicative of quercetin monohexoside, and the hexose could be glucoside or galactoside [ 42 ]. Dissociation of fragment m/z 593 showed a loss of 308 units (corresponding to a rhamnose plus glucose group) and yielded directly a fragment ion at m/z 285 (assigned as kaempferol).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies conducted more than a decade ago focused on the anti-hyperglycemic effects Myr alone (51)(52)(53)(54)(55). A non-controlled, pilot study reported that Eugenia punicifolia (Kunth) DC (Myrtaceae), which is rich in Myr, could be used as adjuvant therapy for T2DM (56). However, a prospective study showed that none of the total flavonols and flavones, quercetin, kaempferol, myricetin, apigenin, or luteolin, were significantly associated with an increased risk of T2DM (57).…”
Section: Discussionmentioning
confidence: 99%
“…Subfractions C9‐4 and C11 were purified by solid phase extraction on Supelclean ™ LC‐18 SPE (6 ml) cartridges ( Sigma‐Aldrich ) eluted with water‐methanol (9:1, v / v ). The purified samples were analyzed by analytical HPLC according to the procedure described by Sales et al . The analytical system comprised a Shimadzu model SPD 20A chromatograph with diode array detector and a Phenomenex Luna C18 reversed phase column (250 × 4.6 mm; 5 μm particle size).…”
Section: Methodsmentioning
confidence: 99%